أثر تطبيق نظام إدارة الجودة على المؤشرات الكمية للأداء الإنتاجي بالمؤسسة الصناعية الحاصلة على شهادة الايزو9001 - نعرورة, بوبكر; بورحومة, عبد الحميد (جامعة الوادي - University of Eloued, 2014)
يعتبر موضوع الجودة وإدارتها من الموضوعات التي حضيت حديثا بدرجة كبيرة من الاهتمام، حيث أنها أصبحت القاسم المشترك في العديد من الكتابات الاقتصادية والإدارية، فأصبحت الجودة في ظل هذه التحديات سلاحا تنافسيا، خصوصا بعد ظهور المواصفات الدولية لأنظمة إدارة الجودة، التي أصبحت المنظمات الصناعية تسعى لتطبيقها و الحصول على شهادة الإيزو من أجل تحسين أدائها و كسب مزايا تنافسية، سنحاول في هذه الدراسة دراسة أثر تطبيق نظام إدارة الجودة على المؤشرات الكمية للأداء الإنتاجي بالمؤسسة الصناعية. The issue of quality and management is one of the topics that have recently been given a great deal of attention as it has become the common denominator in many economic and administrative writings. In these challenges, quality has become a competitive weapon, especially after the emergence of international standards for quality management systems. And to obtain the ISO certificate in order to improve its performance and gain competitive advantages, we will attempt in this study to study the impact of the application of quality management system on the quantitative indicators of production performance in the industrial institution.
مقال
Keywords: الجودة، نظام إدارة الجودة، الإيزو، الأداء الإنتاجي; Quality, quality management system, ISO, production performance